2013
DOI: 10.1016/j.jcin.2012.12.123
|View full text |Cite
|
Sign up to set email alerts
|

The “Final” 5-Year Follow-Up From the ENDEAVOR IV Trial Comparing a Zotarolimus-Eluting Stent With a Paclitaxel-Eluting Stent

Abstract: These data demonstrate the durable efficacy and safety of E-ZES compared with PES for the treatment of de novo coronary lesions. Significant improvements in late safety outcomes were observed with E-ZES but should be considered hypothesis-generating, given the limited statistical power of the trial. (The ENDEAVOR IV Clinical Trial: A Trial of a Coronary Stent System in Coronary Artery Lesions; NCT00217269).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
34
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 75 publications
(37 citation statements)
references
References 28 publications
1
34
1
Order By: Relevance
“…We report a similar probability for TLF with use of E-ZES as compared to 5-year rates of ENDEAVOR IV trial [16] (13.8% vs 14.7%) and similar probability for ARC definite/probable (1.7% vs 1.3% in ENDEAVOR IV). Patients treated with EES, demonstrated lower probability for TLF (7.5% vs 12.7%) and for TLR (3.3% vs 8.6%) at 5 years in compare to rates reported in SPIRIT III trial [17].…”
Section: Discussionsupporting
confidence: 54%
“…We report a similar probability for TLF with use of E-ZES as compared to 5-year rates of ENDEAVOR IV trial [16] (13.8% vs 14.7%) and similar probability for ARC definite/probable (1.7% vs 1.3% in ENDEAVOR IV). Patients treated with EES, demonstrated lower probability for TLF (7.5% vs 12.7%) and for TLR (3.3% vs 8.6%) at 5 years in compare to rates reported in SPIRIT III trial [17].…”
Section: Discussionsupporting
confidence: 54%
“…It seems that the type of drug, and specifically modification of the release profile, plays more pronounced role. Fast-release ZES (Endeavour, Medtronic) has shown a significant difference in clinical performance against paclitaxel-eluting stents (PES), as shown by significant risk reduction in late and very late stent thrombosis, cardiac death, and myocardial infarction [14,15]. On the other hand, at longer follow-up the excellent safety profile did not translate into efficacy, with inferior rates of angiographic surrogates of restenosis and target vessel failure when compared to SES and PES [15][16][17].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, a zotarolimus-eluting stent was associated with a lower rate of cardiac adverse events than a sirolimus-eluting stent in very late stent thrombosis after three years of follow-up [31]. However, Camenzind et al reported no difference in clinical outcomes at one year between Endeavor and Taxus stents, although the Endeavor stent had a significantly lower rate of stent thrombosis between one and five years [32]. The ZEST trial also showed that the Endeavor stent had better outcomes than a sirolimus-eluting stent, but similar results to a paclitaxel-eluting stent after one year of follow-up [33].…”
Section: Second Generation Dessmentioning
confidence: 99%